Who are the Canaanites?‎ New Contexts and Concepts - Zakarneh, Faisal Saeed (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to provide an alternative perspective on the definition of the Canaanites, their origins, and their fate, within the framework of new contexts and concepts introduced by modern critical methodologies focused on renewal, especially in relation to history and archaeology. The research seeks to rely on scientific and credible historical sources to obtain data and information about the Canaanites and their history. Methods: The research adopts a new approach based on genetic genealogy and genetic engineering, in addition to modern methodologies in the fields of history and archaeology. Results: The research highlights the weakness and lack of credibility of classical literature and studies regarding the nature and definition of the Canaanites, particularly those influenced by biblical narratives. In contrast, the research emphasizes the importance of the opposing perspectives provided by critical intellectual approaches from the school of biblical archaeology, although these perspectives have not yet offered definitive conclusions on the subject. Conclusion: The research concludes with a definitive definition of the Canaanites in terms of their origins and fate, based on modern genetic studies, as well as findings from recent, neutral historical and archaeological research. These studies have scientifically proven that the Canaanites were an indigenous people in their land, known as the land of Canaan (present-day Levant), and that they are the natural and biological descendants of their Natufian ancestors. Furthermore, the Canaanites were not exterminated or eradicated, but their presence continued through the contemporary populations of the Levant up to the present day.